Pertimbangan Hukum Hakim Terhadap Putusan Bebas Dalam Tindak Pidana Pembunuhan (Studi Putusan Nomor : 454/Pid.B/2024/PN. Sby) - Pedan, Yohanis Egi; Adam, Sherly; Latupeirissa, Julianus Edwin (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The judge's legal considerations are a stage in which the panel of judges comprehensively assesses the facts revealed during the trial process based on legal and non-legal considerations as the basis for a decision that embodies the value of justice.Purposes of the Research: This study aims to analyze and discuss the legal considerations of judges in acquittal verdicts for criminal homicide in verdict number: 454/Pid.B/2024/PN.Sby and to analyze and discuss acquittal verdicts for perpetrators of criminal homicide from the perspective of the objectives of criminal punishment.Methods of the Research: The research method used is normative legal research using a legislative approach, conceptual approach, and case approach. The legal materials used are primary, secondary, and tertiary legal materials. The procedure for collecting legal materials is carried out through literature study, processed through editing, systematization, and qualitative analysis.Results / Findings / Novelty of the Research: The results of the study show that the judge's legal considerations regarding the perpetrator of the crime of murder in decision number: 454/Pid.B/2024/PN. Sby, based on the judge's legal considerations of all elements of the alternative charges under Article 338 of the Criminal Code, Article 351 paragraph (3) of the Criminal Code, Article 359 of the Criminal Code, and Article 351 paragraph (1) of the Criminal Code, which were brought by the public prosecutor against the defendant Gregorius Ronald Tannnur, were not legally proven. The reason for this was that the judge was convinced by the opinion of a driving safety expert that the victim was outside the lane of the car driven by the defendant and, based on CCTV footage that did not clearly show that the victim died as a result of murder or being run over by the defendant's car, the judge acquitted the defendant. An acquittal of a perpetrator of a criminal act of murder is contrary to the purpose of punishment if it is not based on strong evidence. If an acquittal is given because the judge was not careful in examining the evidence and witnesses or for other reasons that are not in accordance with the law, then this verdict can be considered unfair and can reduce public trust in the judicial system to provide justice and protect the community